KAJIAN KINERJA DINDING PENGARAH REMBESAN DAN TES PERMEABILITAS DIAFRAGMA WALL PADA HILIR BENDUNGAN TUGU - Baskara, Rizki Dwi; Solikin, Mochamad; Sunarjono, Sri; Harnaeni, Senja Rum (Politeknik Negeri Semarang, 2023)
On the inside of the dam, there is a seamless instrumentation. V-Notch is one of thestandard dam safety instruments used to measure water dam seepage discharge. Theporous soil and high permeability around the V-Notch cause water seepage to notbe directed properly to the V-Notch. If it is not directed properly then the erosion ofthe reed or piping cannot be detected. So we need a construction design of thebarrier wall for collecting water seepage, namely the wall diaphragm wall. Thepurpose of this research is to analyze the material, evaluate the performance, andcompare the diaphragm wall. The method used is falling head test, monitoringobservation well (OW), direct observation method when working. The results of thedownstream wall diaphragm material permeability test using the fall head test showthat the largest permeability coefficient value is 1.3 x 10-5cm/sec. where this valuehas reached a low coefficient of permeability. Results Downstream wall diaphragmperformance based on groundwater level at OW.8 < from OW.7. Downstreamdiaphragm wall or water seepage collection barrier can be said to work well. Fromthe analysis method, the diaphragm wall is easier to work than using the Clay heapmethod. This is proven because the diaphragm wall method can be carried out in therainy season and dry season. From the time calculation analysis, it is known that itis faster to use the diaphragm method with an estimated working time of 4 months 2days using 1 tool. As for the estimated length of time working with Clay soil piles is7.5 months using 1.5 tools. Based on the calculation of the cost of drilling plasticconcrete is more expensive than the Clay heap method. The cost of diaphragm wallis Rp. 9,581,703,257.38. and the cost of Clay is Rp. 8,742,490,556.95.